Promoting Commercial Security According to Mangala Sutta Principles - Sornton, Anusorn; Phra Srivinayaphon (Journal of Dhamma for Life, 2024)
This research has the following objectives: 1) To study the promotion of trade stability 2) To study the auspicious principles of Buddhism. 3)To analyze the promotion of trade stability according to the principles of the Mangala Sutta. It is a study of the content of primary and secondary documents.The results of the study found that. Promoting trade stability by applying the auspicious principles that are consistent with the 7Ps strategy. The basic principles of doing business are the main elements, including: 1. blameless actions 2. righteous conduct 3. Great learning 4. skill 5. living in a suitable region 6.not to associate with fools 7. to associate with the wise 8. setting oneself in the right course 9. highly trained discipline 10. a livelihood which is free from complications 11. patience 12. well-spoken speech 13. reverence 14. humility. It is both an internal and external factor. Internal factors are a part of planning work to be connected in an orderly manner. It is a unique ability to trade knowledge and understanding in every dimension. As for external factors, those are factors that come from other parts, whether it be trading partners. Economic fluctuation or stability but external factors may be difficult to control, so risks must be prevented. Practicing the Mangala Sutta is a principle that can be applied to all dimensions.From the educational dimension, seeking knowledge Dimensions of life for all career fields and the dimension of developing morality in doing business stably it can be considered a risk prevention the auspicious principles of the Sutta can then be applied or adapted to trade. As a driving force in every dimension to connect with things that will lead to development. To create progress and promote trade to continue to flourish and be stable.